2008
DOI: 10.1016/j.neuropharm.2008.06.057
|View full text |Cite
|
Sign up to set email alerts
|

Cue-induced reinstatement of alcohol-seeking behavior is associated with increased ERK1/2 phosphorylation in specific limbic brain regions: Blockade by the mGluR5 antagonist MPEP

Abstract: Relapse to alcohol use after periods of abstinence is a hallmark behavioral pathology of alcoholism and a major clinical problem. Emerging evidence indicates that metabotropic glutamate receptor 5 (mGluR5) antagonists attenuate relapse to alcohol-seeking behavior but the molecular mechanisms of this potential therapeutic effect remain unexplored. The extracellular signal-regulated kinase (ERK 1/2 ) pathway is downstream of mGluR5 and has been implicated in addiction. We sought to determine if cue-induced reins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
115
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(130 citation statements)
references
References 93 publications
(106 reference statements)
14
115
1
Order By: Relevance
“…Our study also lends mechanistic confidence to previous reports that have used pharmacological tools to identify a role of mGluR5 in behaviors maintained by reward-paired stimuli (Tessari et al, 2004;Bespalov et al, 2005;Bäckström and Hyytiä, 2006;Schroeder et al, 2008;Gass et al, 2009;Kumaresan et al, 2009;MartinFardon et al, 2009;O'Connor et al, 2010), since these reports could have reflected off-target (Olive, 2009), anhedonic (Bäckström and Hyytiä, 2007) or reinforcing (van der Kam et al, 2009) effects of the pharmacological tools used.…”
Section: Discussionsupporting
confidence: 79%
“…Our study also lends mechanistic confidence to previous reports that have used pharmacological tools to identify a role of mGluR5 in behaviors maintained by reward-paired stimuli (Tessari et al, 2004;Bespalov et al, 2005;Bäckström and Hyytiä, 2006;Schroeder et al, 2008;Gass et al, 2009;Kumaresan et al, 2009;MartinFardon et al, 2009;O'Connor et al, 2010), since these reports could have reflected off-target (Olive, 2009), anhedonic (Bäckström and Hyytiä, 2007) or reinforcing (van der Kam et al, 2009) effects of the pharmacological tools used.…”
Section: Discussionsupporting
confidence: 79%
“…Recent findings provide strong evidence that mGluR 2/3 participate in mediating many addiction-relevant actions of ethanol. Specifically, mGluR 2/3 have been shown to play a role in the reinforcing effects of ethanol (Backstrom et al, 2004;Backstrom and Hyytia, 2005;Besheer et al, 2010;Gass and Olive, 2009;Olive et al, 2005;Sidhpura et al, 2010), withdrawal states (Blednov and Harris, 2008;Sidhpura et al, 2010), and processes that convey vulnerability to relapse (Adams et al, 2010;Backstrom et al, 2004;Rodd et al, 2006;Schroeder et al, 2008;Sidhpura et al, 2010;Zhao et al, 2006). The effects of mGluR 2/3 manipulation in animal models of these aspects of ethanol addiction are suggestive of significant treatment target potential (Heilig and Egli, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This model also exhibits predictive validity, as drugs such as naltrexone that decrease relapse in abstinent drug users also decrease reinstatement of drug seeking behavior in rats (Comer et al, 2006) As mentioned previously, drug-associated cues induce ERK phosphorylation in components of the mesocorticolimbic system (L. Lu et al, 2005;Miller, et al, 2005) and ERK has been shown to play a role in drug-induced and synaptic plasticity (G. M. Thomas, et al, 2004;Valjent, Corvol, et al, 2006) thus it is not surprising that evidence exist that support a role for ERK in cue-elicited reinstatement of drug-seeking. Cue-induced reinstatement of alcohol-seeking is associated with enhanced activation of ERK in the BLA and NAc shell (Schroeder et al, 2008). The mGlu5 receptor antagonist 2-Methyl-6-(phenylethynyl)pyridine (MPEP) was shown to block both the cue-induced drug-seeking and the associated increase in phospho-ERK (Schroeder, et al, 2008), indicating that ERK activation is dependent on mGlu5 receptor signalling and plays a key role in the effect of MPEP on drug-seeking.…”
Section: The Role Of Mapk In the Reinstatement Model Of Drug-seekingmentioning
confidence: 99%
“…Cue-induced reinstatement of alcohol-seeking is associated with enhanced activation of ERK in the BLA and NAc shell (Schroeder et al, 2008). The mGlu5 receptor antagonist 2-Methyl-6-(phenylethynyl)pyridine (MPEP) was shown to block both the cue-induced drug-seeking and the associated increase in phospho-ERK (Schroeder, et al, 2008), indicating that ERK activation is dependent on mGlu5 receptor signalling and plays a key role in the effect of MPEP on drug-seeking.…”
Section: The Role Of Mapk In the Reinstatement Model Of Drug-seekingmentioning
confidence: 99%